Genome Size of 17 Species From Caelifera (Orthoptera) and Determination of Internal Standards With Very Large Genome Size in Insecta - Mao, Ying; Zhang, Nan; Nie, Yimeng; Zhang, Xue; Li, Xuejuan; Huang, Yuan (Frontiers in Physiology, 2020)
Comparative studies of insect genome size show that Orthoptera is a unique group of Insecta with a significantly enlarged genome. To determine a suitable internal standard for a large genome, and to compare the effects of different internal standards on estimates of genome size, we used four internal standards to estimate nuclear DNA content in nine insect species with large genomes. The results showed that the combination of two internal standards, Locusta migratoria (♂1C = 6.20 pg, ♀1C = 6.60 pg) and Periplaneta americana♂ (1C = 3.41 pg), was suitable for estimating large genome of Caelifera by flow cytometry. Using these two internal standards, we estimated the genome sizes of 17 species of Caelifera (12 genera in Acrididae, 2 genera in Pamphagidae, 1 genus in Pyrgomorphidae) using flow cytometry. Genomes ranged from 6.57 pg (Shirakiacris shirakii) to 18.64 pg (Bryodemella holdereri), the largest described in insects to date. These species showed significant genomic dimorphism based on sex: females had a 0.56 pg larger genome than males on average, which might be due to the sex chromosome determinism mechanism of X0(♂)/XX(♀). To test the results obtained by flow cytometry, we used k-mers of Illumina sequencing data to gauge the C-value of Calliptamus abbreviatus and Haplotropis brunneriana. The results of the two methods are slightly different. Genomes were estimated to be about 0.28 and 0.26 pg smaller, respectively, than the flow cytometry values. Furthermore, we also reconstructed the evolutionary relationships of these taxa and discuss the genome size evolution in a phylogenetic framework.